The management of public safety in the municipality of Currais Novos – RN (Research, Society and Development, 2019)
The present study has the objective of analyzing the perception of the candidate approved in the contest of the military police on public safety management in new corrals RN. This is a qualitative study applied through an instant messaging application, with a subject who knows the area of public security. The study revealed that the Rio Grande do Norte state military police are scrapped, and for lack of investment in the last ten years in the area criminal organizations have grown rapidly in the state. Thus, the study concludes that the perception about the management of public security in the state RN, is a poor management and that the lack of investments in personnel and equipment that led to an increase in urban and rural violence.